Factors predicting transrectal ultrasound-guided systematic prostate biopsy failure - Çetin, Serhat; Olgun, Ahmet; Bulut, Ender Cem; Koparal, Murat; Bayramli, Elbay; Şen, İlker and Sözen, Sinan (The European Research Journal, 2023)
Objectives: To determine the factors that predict the failure of systematic prostate biopsy by examining the clinical, laboratory, and radiological parameters of patients for whom prostate cancer was detected by magnetic resonance imaging (MRI)-targeted biopsy but not by systematic biopsy. Methods: Patients were included in this study if they had undergone combined targeted and systematic biopsy and had cancer detected in the targeted biopsy. They were biopsy-naive patients and had lesions with a Prostate Imaging Reporting and Data System (PIRADS) score ≥ 3 in the peripheral zone on MRI. The clinical, biochemical, and radiological findings of the groups with and without cancer detected in the systematic biopsy were compared. Results: A total of 100 patients had an index lesion in the peripheral zone and cancer detected by MRI-targeted biopsy. In 43 (43%) of the patients, no cancer was detected in the systematic biopsy, whereas it was detected in the other 57 (57%). Statistically significant differences were found between the two groups in terms of prostate volume and PSA density (p < 0.001 and p < 0.001, respectively). Moreover, the findings of univariate and multivariate logistic regression analyses indicated that prostate volume and lesion size are independent predictors of systematic biopsy failure. Conclusions: The success of systematic biopsy may be lower in patients with high prostate volume and low peripheral zone index lesion size.